HUBUNGAN TINGKAT PENGETAHUAN NEDDLE STICK INJURY DENGAN SIKAP PENCEGAHAN KEJADIAN NEDDLE STICK INJURY PADA MAHASISWA D4 KEPERAWATAN ANESTESIOLOGI UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Rahmadani, Dian Ayu; Purnamasari, Vita (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Anesthesiology nursing clinical learning is a basic experience for honing abilities and skills. Students are at high risk of injury if they do not implement work safety procedures correctly. Neddle Stick Injury (NSI) is an accident involving a syringe that is contaminated with the patient's body fluids and can cause work safety problems. Knowledge and attitudes towards preventing NSI are very important things to know and do to reduce the incidence of NSI and the risk of nosocomial infections. Objective: The study aimed to determine the correlation between the level of NSI knowledge and attitudes towards preventing NSI incidents in D4 Anesthesiology Nursing students. Research Method: This research applied a quantitative research with a cross sectional approach to sampling using Simple Random Sampling. The sample consisted of 60 respondents. Results: The results of the test on the relationship between knowledge and attitude towards preventing NSI using the Kendall Tau test showed significant results with a (p) value of 0.000 (p < 0.05) and a strong correlation coefficient value, namely (r) = 0.638**. Conclusion: There is a relationship between the level of NSI knowledge and the attitude towards preventing NSI in D4 Anesthesiology Nursing students at Universitas 'Aisyiyah Yogyakarta. Suggestion: It would be better to add learning media related to NSI or work safety and to carry out regular supervision of students who are about to undergo clinical practice for the first time.